Tips practicos de EKG en niños: Tips practicos de EKG en niños - Carvajal-Barrios, Gustavo; Matiz-Mejía, Sandra; Vanegas- Gascón, Edgardo; Bustillo-Zarate, Francisco (Pediatría, 2024)
Presentamos el póster de tips para la lectura de EKG en niños.